Nationalism education in elementary school: A systematic literature review - Bherrio Dwi Saputra; Mukhamad Murdiono; Entoh Tohani (Institute of Advanced Engineering and Science, 2023)
This article aims to present a literature review on nationalism education in Elementary School in the latest literature because there are still few who research it. This research applies the systematic review literature method with the preferred reporting items for systematic reviews and meta-analysis (PRISMA) protocol. The research stages include identification, screening, eligibility, inclusion, and analysis presentation utilizing the help of the Publish or Perish 7 application, VOSviewer, and NVIVO 12 Plus. The results of searching for articles according to the theme in Scopus through the Publish or Perish 7 application there are 226 articles which are filtered into 50 selected papers. The topic findings are character education, education, architectural education, democratic parenting, nationalism attitude, character building, international education, digital citizenship, acculturation, literacy, citizenship education, traditional games, national education, de-colonialism, ethnicity, implementation of character education reinforcements, ethno-nationalism, and curriculum. The research findings mention that nationalism education in elementary schools is a conscious effort of educational institutions to instill students’ understanding, knowledge, and attitudes to love and defend the country implemented through civics, social studies, and character education, which has an impact on character building, students’ love for language, culture and the integrity of the country. Future research needs to examine nationalism education in elementary schools according to approaches, strategies, media, materials, technological developments, and research trends.